2013
DOI: 10.1590/s1516-18462013000400017
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimento sobre a gagueira na cidade de Salvador

Abstract: OBJETIVO: verificar o conhecimento sobre a gagueira entre moradores da cidade de Salvador. MÉTODO: trata-se de um estudo descritivo, de corte transversal e natureza quantitativa com a participação voluntária de residentes da cidade de Salvador. Todos responderam ao questionário de Atenção à Gagueira e foram equiparados quanto ao gênero, idade e escolaridade. RESULTADOS: das 417 pessoas entrevistadas 78,2% afirmaram ter visto ou conhecer pessoas que gaguejam; 52,2% relataram que a pessoa com gagueira pertencia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 13 publications
7
3
1
Order By: Relevance
“…The data indicated that most respondents believed to be a high prevalence of the disorder in the general population. This same finding was shown in previous studies (7)(8)(9)(10)(11) . The discrepancy in the number of people who stutter in the population may indicate a misconception on the subject stuttering.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The data indicated that most respondents believed to be a high prevalence of the disorder in the general population. This same finding was shown in previous studies (7)(8)(9)(10)(11) . The discrepancy in the number of people who stutter in the population may indicate a misconception on the subject stuttering.…”
Section: Discussionsupporting
confidence: 92%
“…As for the professional responsible for the treatment, although educators believe that stuttering is emotional cause, most of them consult an audiologist if you had a child with stuttering. This result is consistent with the literature, which describes the audiologist as the most sought professional to evaluate children with stuttering (4,(7)(8)(9)(10)(11) .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations